2005
DOI: 10.1111/j.1365-313x.2005.02478.x
|View full text |Cite
|
Sign up to set email alerts
|

Two adjacent nuclear genes are required for functional complementation of a chloroplast trans‐splicing mutant from Chlamydomonas reinhardtii

Abstract: SummaryThe chloroplast tscA gene from Chlamydomonas reinhardtii encodes a co-factor RNA that is involved in transsplicing of exons 1 and 2 of the psaA mRNA encoding a core polypeptide of photosystem I. Here we provide molecular and genetic characterization of the trans-splicing mutant TR72, which is defective in the 3¢-end processing of the tscA RNA and consequently defective in splicing exons 1 and 2 of the psaA mRNA. Using genomic complementation, two adjacent nuclear genes were identified, Rat1 and Rat2, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
55
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 47 publications
(56 citation statements)
references
References 50 publications
0
55
0
Order By: Relevance
“…Recent analysis of the nuclear pre-mRNA processing machinery revealed that proteins involved in RNA 3Ј-end processing are integral components of supraspliceosomes (44). This is reminiscent of the function of psaA splicing factors Rat2 and Raa1, which are both involved in 3Ј-end processing of the tscA RNA (15,22).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Recent analysis of the nuclear pre-mRNA processing machinery revealed that proteins involved in RNA 3Ј-end processing are integral components of supraspliceosomes (44). This is reminiscent of the function of psaA splicing factors Rat2 and Raa1, which are both involved in 3Ј-end processing of the tscA RNA (15,22).…”
Section: Discussionmentioning
confidence: 99%
“…The RAT2 gene was previously identified in the C. reinhardtii class C trans-splicing mutant TR72:75, which shows a defect in trans-splicing of the chloroplast psaA mRNA and is crucial for 3Ј-end processing of the chloroplast tscA RNA (22). By using Raa4 as a bait, Rat2 was found among subcomplex I proteins (24).…”
Section: Core Components Of Trans-splicing Subcomplexes I and Ii-mentioning
confidence: 99%
See 2 more Smart Citations
“…A remarkable result of our investigation was the detection of the functionally characterized splicing factors Raa1, Raa3, and Rat2, which all are involved in splicing of the first group II intron of the psaA precursor RNA (9,10,51) (Table I). Raa1 is also involved in the splicing of second group II intron of psaA pre-mRNA (52).…”
Section: Discussionmentioning
confidence: 99%